Differential subordination and superordination for certain subclasses of p-valent functions - Shenan, Jamal M.; Galiz, Ahmed S. (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper, we study applications of the differential subordination and superordination of analytic p-valent functions in the open unit disc associated with certain operator defined by the Wright generalized hypergeometric function. Sandwich-type result involving this operator is also derived.